UAV Formation Flight Based on Nonlinear Model Predictive Control. (2nd February 2012) - Chao, Zhou; Zhou, Shao-Lei; Ming, Lei; Zhang, Wen-Guang
Abstract : We designed a distributed collision-free formation flight control law in the framework of nonlinear model predictive control. Formation configuration is determined in the virtual reference point coordinate system. Obstacle avoidance is guaranteed by cost penalty, and intervehicle collision avoidance is guaranteed by cost penalty combined with a new priority strategy.